Penguatan Literasi Anti-Bullying Remaja Melalui Edukasi Komprehensif Berbasis Media Visual Interaktif - Salawali, Siti Hajar; Hiola, Dewi Suryaningsi; Auli Irfah; Hunawa, Rachmawaty D; Arsad, Sitti Fatimah Meylandri (Jurnal Pengabdian, 2025)
Bullying remains a pressing global issue, particularly among adolescents in educational settings. This community service program was designed to enhance students' knowledge and awareness of SMK Tridharma Lab School UNG regarding the definitions, causes, types, impacts, warning signs, prevention strategies, and appropriate responses to bullying. A structured, one-day intervention was conducted using interactive educational methods supported by visual media, including PowerPoint presentations, animated videos, thematic posters, and a practical pocket guidebook. A total of 28 students actively participated in thematic sessions, group discussions, and reflective activities. The effectiveness of the intervention was evaluated using pre- and post-activity questionnaires. The results indicated a significant improvement across all indicators: 95% of participants demonstrated accurate understanding of the concepts, types, and prevention strategies, while 90% showed a solid grasp of the causes and consequences of bullying. These findings emphasize the effectiveness of multimodal, youth-centered educational strategies in fostering anti-bullying literacy. The program highlights the importance of integrating innovative visual media into community engagement efforts to promote safer, more inclusive school environments.